Karakteristik Pasien Tonsilitis pada Tonsilektomi di Rumah Sakit Pertamina Bintang Amin Bandar Lampung - Festy Ladyani Mustofa; Ika Artini; Dellylah Nurmawati (Puslitbang Sinergis Asa Professional, 2020)
Tonsillitis is an inflammation of the palatine tonsils originating from the Waldeyer ring. Eustachian tubal tonsils, lingual tonsils, palatine tonsils, and pharyngeal tonsils are the composition of the lymph glands in the oral cavity and are the waldayer ring's composition. Tonsillectomy is one type of ENT (Ear Nose and Throat) surgery most often performed on children, adolescents, and adults. Tonsillectomy is also a procedure that can be done if there is a chronic infection or a recurring infection. This study aims to determine the characteristics of age, sex, tonsillar size of Tonsillitis patients in Tonsillectomy at Pertamina Bintang Amin Hospital in Bandar Lampung. Method: The research method used is a quantitative descriptive analysis method with data taken retrospectively. The source of the research data is secondary data obtained from medical records of patients diagnosed with Tonsilitis in Tonsillectomy at Pertamina Bintang Amin Hospital in Bandar Lampung. A total of 92 patients. Data collection in November 2019 - finished. Analysis through univariate analysis. The results show the characteristics of Tonsillitis Patients in Tonsillectomy in Pertamina Bintang Amin Hospital are 12-25 years of age (52.5%) and 6-11 years of age 30 (3 2.6%) and ages 26-45 5 years (5.4%) and ages 46 - 65 years 3 (3.3%), with 50 (54.3%) female and 42 (45.3%) men, with T3 tonsil size was 47 (51.1%), and T2 size was 27 (29.3%), and T4 was 18 (19.6), and T1 was 0 (0%). Characteristics of Tonsillitis Patients in Tonsillectomy at Pertamina Bintang Amin Hospital in Bandar Lampung, the most age was 12-25 years old, and the most sex is in women, the most tonsil size in T3 size was 47 people.